Reseñas y comentarios - Cuadernos de Economía Revista (Cuadernos de Economía, 1994)
Romer, David. ''The New Keynesian Sinthesis", Journal ofEconomic Perspectives, v. 7, n. 1, invierno de 1993, 7-22. / Tobin James. "Price Flexibility and Output Stability: An Old Keynesian View", joumal 0f Economic Perspectives, v. 7, n. 1, invierno de 1993, 45-65. / Greenwald, Bruce y Stiglitz, Joseph. "New and Old Keynesians", journal of Economic Perspectives, v. 7, n. 1, invierno de 1993, 23-44. / Bénassy, jean-Pascal. "Nonclearing Markets: Microeconomic Concepts and Macroeconomic Applications", joumal of Economic Literature, junio de 1993, 732-761. / King, Robert G. ''Will the New Keynesian Macroeconomics Resurred the IS-LM Model ?", joumal of Economic Perspectives, v. 7, n. 1, invierno de 1993, 67-82. / Mullineux, A. YDickinson, D. "Equilibrium Business Cycles: Theory and Evidence", joumal of Economic Surveys, v. 6, n. 4, 1992,321-358. / Cheng, L Y Dinopoulos, E. "Schumpeterian Growth and Intemational Business Cycles", The American Economic Review, Papers and Proceedings, mayo de 1992, 409-414. / Shaghil, A., Barry, W. et al. "Intemational Business Cyeles", The American Economic Review, v. 83,n. 3, junio de 1993. / Beaudry, Paul y Koop, Gary. ¿Cambian las recesiones permanentemente el producto?", Journal of Monetary Economics 31, 1993, 149-163. / Mullineux, A. YPeng, W. "Nonlinear Business Cycle Modelling", Joumalof Economic Suroeus, v. 7, n. 1, 1993, 41-83. / Shi, He-Ling. "Continuum of Equilibria and Business Cycles: A Dinamic Model of Mesoeconomics", The American Economic Review, v. 82, n. 2, mayo de 1992. / Saint-Paul, G. "Productivity Growth and the Structure of Business Cycle", European Economic Review, v. 37, mayo de 1993, 861-890. / joumal of Political Economy, v 101, n. 3, junio de 1993, 385-409. / Fukao, Kyoji y Otaky, Masayuki. "Accumulation of Human Capital and the Business Cycle", joumal of Polítical Economy, v. 101, n. 1, febrero de 1993, 73-99. / Hausman, Daniel M. y McPherson, Michael S. ''Taking Ethics Seriously: Economics and Contemporary Moral Philosophy", journal of Economic Literature, v. XXXI, junio de 1993. / Bowles, Sarnuel y Gintis, Herbert. ''The Revenge of Horno Econornicus: Contested Exchange and the Revival of Political Econorny", journal of Economic Perspectives, v. 7, n. 1, invierno de 1993.